2012
DOI: 10.1007/s40140-012-0006-1
|View full text |Cite
|
Sign up to set email alerts
|

Anesthesia and Apoptosis in the Developing Brain: An Update

Abstract: There is an increasing concern regarding the risk of anaesthetic neurotoxicity in children. Numerous animal and in vitro studies have demonstrated that general anaesthetics cause a variety of potentially harmful effects on the developing brain. An increased level of neuronal apoptosis is one such effect. In some studies, exposed animals have experienced long-lasting neurobehavioural changes. These effects occur at very specific stages of development and are dose-dependent. There are several plausible mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
2
1
Order By: Relevance
“…(14) Sedation increases scan costs and may cause respiratory depression, inability to maintain an open airway, cardiac arrest, prolonged restlessness, emergence delirium, post-sedation agitation and longterm harmful effects on the developing brain, such as behavioral and cognitive impairment. (14,29,30) Findings of this study do not support the diagnostic performance of CO-RADS reported in adults. However, our results are consistent with the literature regarding CO-RADS and chest CT score inter-rater reliability.…”
Section: ❚ Resultscontrasting
confidence: 94%
“…(14) Sedation increases scan costs and may cause respiratory depression, inability to maintain an open airway, cardiac arrest, prolonged restlessness, emergence delirium, post-sedation agitation and longterm harmful effects on the developing brain, such as behavioral and cognitive impairment. (14,29,30) Findings of this study do not support the diagnostic performance of CO-RADS reported in adults. However, our results are consistent with the literature regarding CO-RADS and chest CT score inter-rater reliability.…”
Section: ❚ Resultscontrasting
confidence: 94%
“…GABA agonists and NMDA receptor antagonists may trigger apoptosis exponentially. Several studies have proven the association between mayor neonatal surgery, cardiac surgery, esophagus atresia repair, laparotomy or hernias, which have been correlated with poor neuronal development when compared with healthy children controls not submitted to anesthetic agents [8]. Children submitted to correction of esophagus atresia during the neonatal stage have experienced learning problems and behavior disorders in the following years, remembering that many of these children were premature, thereby presenting other congenital defects, originating longer neonatal intensive care units hospitalizations and possibly multiple anesthetic episodes.…”
Section: Clinical Evidence On Humansmentioning
confidence: 99%
“…This is a prospective randomized controlled trial of neurodevelopmental outcome after an awake regional anaesthetic or a sevoflurane general anaesthetic plus a regional block in neonates undergoing hernia repair. 12,13 The recruitment phase has been completed with 722 babies studied and follow-up will continue for 5 yr until 2018. Already, however, it is clear that general anaesthesia increases the risk of early apnoea and the need for active interventions for hypotension.…”
Section: The Gas Studymentioning
confidence: 99%